2011
DOI: 10.1007/s10337-011-2077-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic Study of Lung Cancer and the Effects of Radiotherapy on Lung Cancer Patients: Analysis of Highly Polar Metabolites by Ultraperformance HILIC Coupled with Q-TOF MS

Abstract: In this study, plasma samples were collected from 28 health volunteers and 66 lung cancer patients. Ultraperformance HILIC/Q-TOF MS-based metabonomic techniques were employed to compare the highly polar metabolites (HPMs) in the plasma of patients with lung cancer and those in the plasma of healthy volunteers. High separation efficiency and good repeatability of the HILIC/ Q-TOF MS method were observed. Partial least squares discriminant analysis (PLS-DA) of the data from both ESI? and ESI-mode revealed good c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…[3,7,8] Plasma has been profiled for the discovery of biomarkers in cancers. A few examples include hepatocellular carcinoma, [9] pancreatic, [10] epithelial ovarian, [11] prostate, [12] and lung [13] cancers. In these types of experiments metabolites specific to the disease of interest are sought by comparison of results between control and case samples.…”
mentioning
confidence: 99%
“…[3,7,8] Plasma has been profiled for the discovery of biomarkers in cancers. A few examples include hepatocellular carcinoma, [9] pancreatic, [10] epithelial ovarian, [11] prostate, [12] and lung [13] cancers. In these types of experiments metabolites specific to the disease of interest are sought by comparison of results between control and case samples.…”
mentioning
confidence: 99%
“…The authors concluded that the demethylation process could be hampered by radiation, proposing a mechanistic explanation as to why combining radiotherapy with Temozolomide (an alkylating drug) works so efficiently (20). Cai et al monitored metabolic changes in plasma of lung cancer patients treated with radiation, but did not identify possible biomarkers that could distinguish treated from untreated individuals (46). Some studies investigated the effect of surgical intervention on the metabolome (47-51).…”
Section: Resultsmentioning
confidence: 99%
“…This method was also applied to the effect of radiotherapy on highly polar metabolites. Nineteen metabolites were altered at different points during the course of radiotherapy [58]. Serum and plasma metabonomics were developed and tested in patients with small-cell lung cancer.…”
Section: Lung Cancermentioning
confidence: 99%